Application of the GPS reflected signals in tomographic reconstruction of the wet refractivity in Italy. (1st October 2020) - Shafei, Milad Jaberi; Hossainali, Masoud Mashhadi
Abstract: GPS troposphere tomography is one of the most powerful techniques used to extract 3D model of the water vapor and wet refractivity using the observations from local and regional GPS networks. In this technique each unknown parameter is related to the one 3D elements called voxels. This approach is a mixed-determined inverse problem because propagated signals do not pass through some of the voxels. As consequence, the design matrix has rank deficiency and unique solution cannot be reached. To this end, additional constraints are usually applied. In this research as an innovation, we utilized reflected signals from an air-borne reflectometry mission over Italy as additional constraint. According to the obtained results from four distinct parts in DOYs 158 & 160 of 2012, reflected signals help to remove or reduce the rank deficiency of our tomographic models. Due to the lack of radiosonde and radio occultation profiles, to validate the tomographic model results, GPS slant wet delay observations of singular GPS stations within the desired study areas are used as a measure for validation. Depending on the number of reflected and direct signals that we used in our reconstruction area, the range of bias in the developed models change from 1.6 to 6.9 mm. Moreover, the range of RMSE is 30–40 mm. The accuracy and precision of reconstructed images is adequate as far as the mean, minimum and maximum values of the slant wet delays in the test areas of this study are taken into account. Highlights: The rank deficiency of tomographic model could be fixed or improved by using reflected signal as extra constraint. Adding reflectrometry data to the GPS signals supports the uniqueness of solution. First attempt using airborne reflected signals to troposphere tomography.